2011
DOI: 10.1158/1055-9965.epi-10-0847
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Microarray Analysis of Mammary Epithelial Cells from Obese and Nonobese Women at High Risk for Breast Cancer: Feasibility Data

Abstract: Background: Obesity is a well-established risk factor for cancer, accounting for up to 20% of cancer deaths in women. Studies of women with breast cancer have shown obesity to be associated with an increased risk of dying from breast cancer and increased risk of developing distant metastasis. While previous studies have focused on differences in circulating hormone levels as a cause for increased breast cancer incidence in postmenopausal women, few studies have focused on potential differences in the protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Our future proteomic studies will investigate large number of serial and/or bilateral RPFNAs of high-risk women who develop breast cancer to monitor both the cellular and molecular changes and identify potential targets of therapy. We will also validate our future protein expression profiles with immunohistochemistry (IHC) as previously attempted on a selected protein, using limiting RPFNA samples [30]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our future proteomic studies will investigate large number of serial and/or bilateral RPFNAs of high-risk women who develop breast cancer to monitor both the cellular and molecular changes and identify potential targets of therapy. We will also validate our future protein expression profiles with immunohistochemistry (IHC) as previously attempted on a selected protein, using limiting RPFNA samples [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised hierarchical clustering analysis of log 2-transformed values of 52 proteins [30]. Four clusters of proteins ( rows ) were identified in 31 RPFNA cytology samples ( columns ) with (Masood scores ≥15; green ) and without (Masood scores ≤14; yellow ) atypia.…”
Section: Figmentioning
confidence: 99%
“…Manifestation of the obesity signature correlated with shorter time to metastases [52]. However, initial protein microarray data examining alterations in 52 proteins from a small sample of tumours (n = 31) did not show any significantly altered proteins between obese and nonobese subjects after adjustment for false discovery rates, thus preventing translation of these findings into an easily applied tumour protein biomarker panel [53]. In endometrial cancer, gene microarray data revealed different signatures for obese versus nonobese patients with cancer precursor cells, specifically upregulation and activation of the PI3 K pathway in nonobese patients, thus suggesting that different targets are applicable to different patient populations at the same disease site [54].…”
Section: Gene Expression Profiles and Cancer Risk In The Obesementioning
confidence: 91%
“…Given the key role that matrix stiffness plays in regulating PI3K/AKT-signaling, these studies also provide evidence for the convergence of mechanosignaling and redox activation in aggressive cancers. Since AKT-network signaling is active in premalignant tissue from women at high-risk for breast cancer prior to the development of an invasive phenotype (Pilie, Ibarra-Drendall et al 2011; Ibarra-Drendall, Troch et al 2012), this opens the possibility that combination therapies which target both cellular metabolism and tissue stiffness may serve to more effectively halt disease progression.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%